Biologics in steroid resistant nephrotic syndrome in childhood: review and new hypothesis-driven treatment - Angeletti, Andrea; Bruschi, Maurizio; Kajana, Xhuliana; La Porta, Edoardo; Spinelli, Sonia; Caridi, Gianluca; Lugani, Francesca; Verrina, Enrico Eugenio; Ghiggeri, Gian Marco (Frontiers in Immunology, 2023)
Nephrotic syndrome affects about 2–7 per 100,000 children yearly and accounts for less than 15% of end stage kidney disease. Steroids still represent the cornerstone of therapy achieving remission in 75–90% of the cases The remaining part result as steroid resistant nephrotic syndrome, characterized by the elevated risk of developing end stage kidney disease and frequently presenting disease recurrence in case of kidney transplant. The pathogenesis of nephrotic syndrome is still far to be elucidated, however, efficacy of immune treatments provided the basis to suggest the involvement of the immune system in the pathogenesis of the disease. Based on these substrates, more immune drugs, further than steroids, were administered in steroid resistant nephrotic syndrome, such as antiproliferative and alkylating agents or calcineurin inhibitors. However, such treatments failed in inducing a sustained remission. In last two decades, the developments of monoclonal antibodies, including the anti-CD20 rituximab and inhibitor of B7-1 abatacept, represented a valid opportunity of treatment. However, also the effectiveness of biologics resulted limited. We here propose a new hypothesis-driven treatment based on the combining administration of rituximab with the anti-CD38 monoclonal antibody daratumumab (NCT05704400), sustained by the hypothesis to target the entire B-cells subtypes pool, including the long-lived plasmacells.